Efficacy of regional analgesia techniques in abdominal surgery patients with obesity - S. I. Vorotyntsev; M. B. Hrynovska; M. M. Sofilkanych; O. V. Zakharchuk (Zaporozhye State Medical University, 2018)
Abstract The use of regional anesthetic techniques in abdominal surgery is an essential component of the multimodal approach to perioperative analgesia, yet data on their use in obese patients remains limited. The aim of this study is to determine the effectiveness of the epidural analgesia (EA) and the transversus abdominis plane block (TAP-block) in laparoscopic obese patients, as well as to evaluate the possibility of using the rectus sheath block (RSB) as a "rescue" anesthetic technique after laparotomy in obese patients. Materials and methods. The data on the 102 obese patients operated on esophageal hiatal diaphramgmatic hernia, colon tumor, postoperative ventral hernia, morbid obesity and choledocholithiasis were analyzed. In laparoscopic surgery 20 patients received EA (EA group), 21 patients - TAP-block (TAP group), 21 patients - opioids and non-steroidal anti-inflammatory drugs (NSAIDs) without any regional anesthesia techniques (group TIVA1). In laparotomic surgery 16 patients received RSB (RSB group) and 24 patients - only opioids and NSAIDs (TIVA2 group). After the surgery the following was estimated: the time of extubation, the total dose of opioids, the level of pain according to the 10-point numeric range score (NRS), the incidence of dyspnea using the monitor Utas 300 (Ukraine), the incidence of postoperative nausea and vomiting (PONV), the time of active patient mobilization, and the level of satisfaction with analgetic regimen. For the RSB group, the complexity of the RSB and the mean time to achieve adequate analgesia (pain intensity ≤3 points per NRS) were determined additionally. The statistical analysis was performed using the Statistica for Windows version 6.0 software. Results. In the EA group, the intraoperative dose of fentanyl was twice lower, and patients were extubated two times faster than in the TAP, TIVA1, RSB, TIVA2 groups (P < 0.05). At the same time, none of the patients in the EA group required the restoration of neuromuscular conduction with neostigmine (P < 0.05). After the surgery, the pain level was 2-3 times higher in the TIVA1, RSB, and TIVA2 groups than in the EA and TAP groups (P < 0.05). "Rescue" analgesia in the RSB group was performed from the first attempt in all the patients in 5-10 minutes and provided an adequate effect in 3 (2-4) min. The complexity level of RSB was defined as "easy" in 12 (75 %) patients, as "average" in 4 (25 %) patients (P < 0.05). The incidence of dyspnea and opioid doses after surgery in the EA, TAP and RSB groups of patients were 2 times lower, and the incidence of PONV was 3 to 4 times lower than in the TIVA1 and TIVA2 patients' groups (P < 0.05). In the EA and TAP groups, patients became mobile after 8-13 hours after surgery, in the group TIVA1 - after 16-22 hours, in the group RSB - after 18-36 hours, in the group TIVA2 - after 48-96 hours (P < 0.05). 100 % of the respondents from the EA, TAP and RSB groups were satisfied with the analgesic regimen at the "excellent - good" level. In the TIVA1 and TIVA2 groups, 20-25 % of respondents identified analgesic comfort as "good", 60-65 % of respondents - as "satisfactorily", about 15 % of respondents - as "unsatisfactorily" (P < 0.05). Conclusions. In laparoscopic surgery the use of EA or TAP-block in obese patients significantly reduces the level of postoperative pain, the need for opioids, the incidence of dyspnea and PONV, which leads to the possibility of patients' mobilization within 8-13 hours after surgery. After laparotomic surgery in obese patients RSB effectively "rescues" from pain and prevents excessive use of opioids, which reduces the number of adverse reactions and increases satisfaction with the quality of analgesia.